A Three-Gap Analysis of Malaysian Economy - Abdul Malik Thanoon, Marwan (2000)
Malaysia, setting out to transform its economy through industrialisation to become a fully developed country by 2020 must provide for all of the resources required as best as it can. The key question pertaining to economic growth goal in Malaysia is the present and future configuration of the resource gap constraints which can be influenced by factors such as reliability of foreign capital inflow, strength of crowding in and crowding out effects, and the imperatives of the constraints on the process of economic development. This thesis attempts to elucidate the above mentioned structural questions, to identify their solutions as well as to examine the extent of macroeconomic constraints faced by Malaysia as it undertakes economic transformation. Two as well as three-gap approaches have been utilised to identify the dominant resource constraints limiting the target growth and to estimate the future resource requirements needed to achieve the pre-determined target. Particular attention is given to the impact of foreign transfers on the rate of growth in potential output. In addition, the study will examine the saving behaviour of the Malaysian economy. This will be done using the multivariate cointegration approach followed by an error-correction modelling to investigate the saving behaviour in a dynamic framework. The empirical findings of the saving analyses indicate that maintaining a stable macroeconomic condition is critical for mobilising savings, encouraging domestic investment and laying the foundations for sustained economic growth. Among the macro variables exports and tax level appear to be more significant in explaining the saving rate in Malaysia. A number of other variables including interest rate, dependency ratio and rate of growth are also important. The dependency ratio has been found to exert a negative effect on rate of saving. The empirical results have confirmed the adverse effect of foreign direct investment (FDI) on savings, suggesting that strategies aimed at reducing the FDI (and thus debt burden) would help to raise domestic saving. The results of two-gap analysis tends to conform with that expounded by the Neo-structuralists which claims that the dominant constraint in most developing countries is foreign exchange gap caused primarily by structural disequilibrium or macroeconomic imbalances. The estimation and projections carried out have led to be the inference that the trade constraint has tended to be more binding than the saving constraint. In the three-gap analysis, a sustainable growth of 6.5 per cent per annum would require an investment ratio of 28 per cent, while an 8 per cent of annually would growth require 35 per cent investment ratio over the period 1995-2000. With no change in the ratio of interest payments to potential output, 5.58 per cent of foreign saving (around RM 5 billion) per year would be required for an 8 per cent growth and a 4.1 per cent (around RM 3.2 billion) annual increase would be required for a 6.5 per cent growth rate annually over the period 1995-2000.